Analisis perbandingan penentuan piawaian halal antara Malaysia, Indonesia, Singapura dan Brunei / Norhidayah Pauzi - Norhidayah , Pauzi (2016)
Malaysia, Indonesia, Singapore and Brunei are countries in the MABIMS (The Informal Meeting of Religious Ministries of Brunei, Indonesia, Malaysia and Singapore) council which have collaborated in bringing the halal industry to the international arena. However, differences in the determination of halal standards exist in the four countries which have consequently resulted in the disparity of legal status on a few halal issues. This did not only bring about confusion to the industry and consumers, but also revealed weaknesses in the coordination of fatwa in the four countries. Therefore, this study was conducted to evaluate the factors contribute to the differences in consumerables fatwa on a few halal issues in those countries. Comparison was also made in the determination of halal standards among the four countries. The data gathering methods used in this research were library research and field research whilst the inductive, deductive and comparative methods were used for the data analysis method. The research showed significant differences in areas of fatwa, audit, Halal Assurance System, halal standards and enforcement between the four countries. In the fatwa aspect, it was found that Brunei was bound by the rigidity of the Syafii school of thought in the determination of the halal legal status of a product. Singapore on the other hand has led the rest in the audit aspect whereby it has set up a special body for the purpose of halal auditing. This has helped in speeding up the process of halal certifications. Indonesia has an advantage of a Halal Assurance System which is applied in the Multinational Company, Small and Medium Enterprise (SME) and Micro Industry categories. This has preserved the companies image and enhanced the consumers’ confidence level towards the Halal products further. Malaysia has been recognized at the international level as one of the best in the world in the area of halal standards as it has succeeded in producing a procedure manual and a certain number of halal standards but lacked in terms of enforcement as the law regarding halal standards are non-existent. It is hoped that this study is able to contribute to the harmonization of halal standards in the four countries and subsequently lead to the establishment of a universal halal standard.